Sauchinone controls hepatic cholesterol homeostasis by the negative regulation of PCSK9 transcriptional network - Hee-Sung Chae; Byoung Hoon You; Dong-Yeop Kim; Hankyu Lee; Hyuk Wan Ko; Hyun-Jeong Ko; Young Hee Choi; Sun Shim Choi; Young-Won Chin (Scientific Reports, 2018)
Abstract Whole-transcriptome analysis and western blotting of sauchinone-treated HepG2 cells demonstrated that sauchinone regulated genes relevant to cholesterol metabolism and synthesis. In particular, it was found that the expression of proprotein convertase subtilisin/kexin type 9 (PCSK9) was downregulated, and the expression of low density lipoprotein receptor (LDLR) was upregulated in sauchinone-treated HepG2 cells. Consequently, LDL-cholesterol (LDL-C) uptake was increased. As a transcriptional regulator of PCSK9 expression, sterol regulatory elements binding protein-2 (SREBP-2) was proposed by transcriptome analysis and western blotting. Oral administration of sauchinone increased hepatic LDLR through PCSK9 inhibition in obese mice and showed the reduced serum LDL-C levels and downstream targets of SREBP-2. Thus, it is evident that sauchinone reduces hepatic steatosis by downregulating the expression of hepatic PCSK9 via SREBP-2.